Ritual Mandi Suci di Candi Jolotundo: Integrasi Nilai Pendidikan Islam dan Multikultural - Achmad Firdaus; Askhabul Kirom; M. Jamhuri (Bustanul Ulum Journal of Islamic Education, 2026)
This research explores the values of Islamic education and multicultural Islamic education embedded in the sacred life-water bathing ritual at Jolotundo Temple, East Java. This field research employed a qualitative method with a phenomenological approach to examine the subjective experiences of individuals involved in the ritual. Data were collected through participatory observation, in-depth interviews, and documentation, then analyzed inductively through phenomenological stages and thematic categorization. The findings reveal that the ritual consists of four stages: intention (niyyah), prayer, the bathing process, and final contemplation, symbolizing physical and spiritual purification in line with the concept of tazkiyatun nafs in Islamic education. Referring to James A. Banks’ theory, the ritual reflects five dimensions of multicultural education. Involving participants from diverse religious and cultural backgrounds, the ritual functions as a socio-spiritual learning medium that internalizes tolerance, justice, equality, and acceptance in a pluralistic society. Theoretically, this study expands multicultural Islamic education discourse beyond formal institutions, while practically it may support religious moderation and culture-based Islamic education in multicultural society.